UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN MATOA (Pometia pinnata J.R. Forst. & G. Forst) - Deri Islami; Khoirul Anam Falakhudin; Muslim Suardi (LPPM Universitas Abdurrab, 2024)
Matoa (Pometia pinnata J.R. Forst. & G. Forst) can be used as traditional medicine. The plant contains secondary metabolite compounds such as flavonoids, tannins, terpenoids and saponins that have the ability to inhibit the mechanism of action of bacteria. The purpose of this study was to determine the antibacterial activity of n-hexane, ethyl acetate and ethanol extracts of Matoa leaves against gram-positive bacteria Staphylococcus aureus and Streptococcus mutans and gram-negative bacteria Escherichia coli and Klebsiella pneumonia at concentrations of 70, 50, 30 and 10% using the disc diffusion method, Ciprofloxacin as a positive control and DMSO as a negative control. Statistical test results on 70% concentration of ethyl acetate extract showed average results on the inhibition diameter of Staphylococcus aureus, Streptococcus mutans, Eschericia coli and Klebsiella pneumenia were 10.63, 13.43, 11.23, and 13.26 mm, respectively. Based on the results of this study, it can be concluded that the n-hexane, ethyl acetate and ethanol extracts of Matoa Leaf (Pometia pinnata J.R. Forst. & G. Forst) have the ability to inhibit the growth of gram-positive bacteria Staphylococcus aureus and Streptococcus mutans and gram negative bacteria Escherichia coli and Klebsiella pneumonia, but in the n-hexane extract of matoa leaves is not able to inhibit the growth of Staphylococcus aureus.